A study on entrepreneurial opportunities in digital health-care post-Covid-19 from the perspective of developing countries. Issue 3 (6th September 2021) - Khandelwal, Rahul; Kolte, Ashutosh; Rossi, Matteo
Abstract : Purpose: The Covid-19 pandemic encourages organized structures across health sectors to react to the outbreak and digital health technologies have been identified as promising pillars to respond to the outbreak across the globe. The purpose of this study is to address the scoping review aimed at identifying the innovative entrepreneurial opportunities in digital health-care ecosystems. The study highlights the barriers to digital health in developing countries. The study is a forum for the introduction of entrepreneurship prospects in the Indian sense through other foreign readers in developing countries. Design/methodology/approach: This archival study highlights topical literature to explore successful ways of improving market potential in developed countries with respect to digital health. The research offers insights into how a digital health environment could be applied, provides a trajectory that concentrates on key skills and a creative approach. Findings: Health service providers require developing their competency and skills to accelerate and enhance their entrepreneurial opportunities. Social network dynamics analyzes are particularly helpful in modeling pandemic trends and in tracking post-pandemic digital health needs. The acceptability of digital solutions has to be confronted across developing countries especially in rural areas and a collective public health benefit in form of entrepreneurship to serve the society. Research limitations/implications: The research temporarily indicates a creative solution to entrepreneurship in developed countries that can be applied in today's digital arena. Originality/value: To raise public understanding of the advantages of digital health systems in developed regions, health education and promotion campaigns should be focused. The idea analysis can be useful benchmarks for policymakers rather than digital health jurisdictions. The post-pandemic provides developed countries a great opportunity for advanced technology to expand connectivity and networking to digital health entrepreneurship.